Hypertensive bipolar: chronic lithium toxicity in patients taking ACE inhibitor - Masiran, Ruziana; Abdul Aziz, Mohammad Firdaus (BMJ Publishing Group, 2017)
A patient with bipolar I disorder has been treated with lithium and haloperidol for the last 20 years and received an ACE inhibitor for his hypertension since 9 years ago. Despite regular clinic follow-ups and blood monitoring, he recently developed tremors and delirium. On hospital admission, serum level of lithium was far above toxic level. Mental state examination revealed an anxious and disorientated man with irrelevant speech. Immediate discontinuation of lithium resulted in slow reduction of serum lithium levels and gradual resolution of tremor but his delirium persisted for 2 weeks. His condition took a turn for the worse when he developed acute renal failure and arm abscess. We discussed about lithium toxicity and the vulnerability factors which have induced delirium and renal failure in this patient.